Attempt to improve functional outcomes in supracricoid laryngectomy in T2b and T3 glottic cancers - Leszczyńska, Małgorzata (Eur Arch Otorhinolaryngol, 2014)
The goal of this study was to compare the survival rate and functional outcome of an open partial horizontal laryngectomies, Type IIa and modified Type IIa (OPHL Type IIa and OPHL mType IIa), in treatment of moderately advanced glottic carcinoma. Retrospective analysis. 80 Patients underwent OPHL Type IIa and 27, OPHL modified Type IIa (OPHL mType IIa) between the years 2001 and 2009. Clinical staging was performed according to the UICC criteria (2002). Primary endpoints of study were recurrence rate, and 3- and 5-year survival time. Secondary endpoints were laryngeal functions: respiration, swallowing and voice. There were no significant differences within local and regional recurrence rates, organ preservation rate, 3- and 5-year specific disease survival rates between OPHL Type II and OPHL modified Type IIa. Significantly lower need for temporary (OPHL mType IIa 4/27, OPHL Type IIa 30/80) and permanent tracheostomy (OPHL mType IIa 2/27, OPHL Type IIa 16/80) was found. All but one patient (OPHL Type IIa) achieved unrestricted diet. Significantly differed social eating, this ability gained 25/27 OPHL mType IIa and 54/80 OPHL Type IIa (p < 0.05). Voice handicap index revealed a decrease in quality of life in all areas; OPHL Type IIa and OPHL mType IIa differed significantly (31 and 46 points respectively, p < 0.005). The MPT value (longest pitch) for OPHL Type IIa and OPHL mType IIa lasted 8 s and 10, respectively (p < 0.005). There was no significant difference in oncological outcomes between the two types of OPHL succeeded in the earlier extubation, thus significantly lowering the need for temporary and permanent tracheotomy and providing better long-term swallowing. Although the voice was altered in all observed OPHL patients, modified Type IIa technique proved to be superior to the Type IIa in terms of voice quality. Thus, OPHL modified Type IIa is worth promoting, as long as indications were strictly conformed.